The Impact of Self-Efficacy Training on Goal Setting and Academic Persistence - Popescu, Andreea; Nikolova, Mariana; Nasrin, Sharmin (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: The objective of this study was to evaluate the effectiveness of self-efficacy training on enhancing goal setting and academic persistence among high school students. Methods and Materials: This research employed a randomized controlled trial design with two groups: an experimental group receiving self-efficacy training and a control group with no intervention. Thirty students from Bulgaria were randomly assigned to each group (n = 15). The intervention consisted of twelve structured sessions (45–60 minutes each), designed based on Bandura’s self-efficacy theory and focused on goal setting, self-belief, emotional regulation, and academic strategies. Participants completed validated scales measuring goal setting and academic persistence at pre-test, post-test, and five-month follow-up stages. Data were analyzed using repeated measures ANOVA and Bonferroni post-hoc tests with SPSS-27. Findings: The results indicated significant improvements in both goal setting and academic persistence in the experimental group over time compared to the control group. Descriptive statistics revealed that the experimental group’s mean score for goal setting increased from 45.73 (SD = 5.19) at pre-test to 58.60 (SD = 4.77) at post-test and remained high at follow-up (M = 57.80, SD = 5.12). Academic persistence scores followed a similar pattern, increasing from 34.87 (SD = 4.11) to 42.27 (SD = 3.65) and slightly decreasing to 41.40 (SD = 3.84). Repeated measures ANOVA showed significant main effects for time and group, and a significant interaction effect (p < .001). Bonferroni tests confirmed significant improvements from pre-test to post-test and follow-up (p < .001), with no significant decline between post-test and follow-up. Conclusion: The self-efficacy training program effectively enhanced students’ goal-setting abilities and academic persistence, with lasting effects observed after five months. These results support the integration of psychological skills training into school curricula to promote student motivation and resilience.